Revisiting the 1965 Centenary of the International Telecommunication Union - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2023)
The Journal republishes an historic paper from 1965 by Richard (Dick) Butler, later to become Secretary General (1983–1989) of the International Telecommunication Union, on the ITU and its influence on telecommunications standardisation in Australia during in its first century (1865–1965).